Hello from MrBillDoesMath!
Answer:
f(1) = 14000
f(n) = f(n-1) * (9/10) n >=2
f(4) = 10206
Discussion:
I started with this division:
12600 /14000 = 9/10 which agrees with the second term shown. This suggests that each term is gotten by multiplying its predecessor by 9/10. So
f(1) = 14000
f(n) = f(n-1) * (9/10) n >=2
The next term in the sequence is n = 4 :
f(4) = f(3) * (9/10)
f(4) = ( f(2) * 9/10) * (9/10)
f(4) = ( f(1) * 9/10) * 9/10) * (9/10)
f(4) = 14000 * (9/10)^3 = 10206
Though not asked it appears that f(n) = 14000 * (9/10)^(n-1)
Thank you,
MrB